The central blue straggler population in four outer-halo globular clusters - Beccari, Giacomo; Olczak, Christoph (The astrophysical journal, 2012)
Using Hubble Space Telescope /Wide Field Planetary Camera 2 data, we have performed a comparative study of the Blue Straggler Star (BSS) populations in the central regions of the globular clusters (GCs) AM 1, Eridanus, Palomar 3, and Palomar 4. Located at distances R GC > 50 kpc from the Galactic center, these are (together with Palomar 14 and NGC 2419) the most distant clusters in the halo. We determine their color-magnitude diagrams and centers of gravity. The four clusters turn out to have similar ages (10.5-11 Gyr), significantly smaller than those of the inner-halo globulars, and similar metallicities. By exploiting wide-field ground-based data, we build the most extended radial density profiles from resolved star counts ever published for these systems. These are well reproduced by isotropic King models of relatively low concentration. BSSs appear to be significantly more centrally segregated than red giants in all GCs, in agreement with the estimated core and half-mass relaxation times which are smaller than the cluster ages. Assuming that this is a signature of mass segregation, we conclude that AM 1 and Eridanus are slightly dynamically more evolved than Pal 3 and Pal 4.
Gesehen am 14.11.2018